Proteinase‐activated receptor‐2 blockade inhibits changes seen in a chronic murine asthma model. Issue 2 (11th October 2017) - Asaduzzaman, M.; Davidson, C.; Nahirney, D.; Fiteih, Y.; Puttagunta, L.; Vliagoftis, H.
Abstract: Background: Proteinase‐Activated Receptor‐2 (PAR2 ) is a G protein‐coupled receptor activated by serine proteinases. We have shown that PAR2 activation in the airways is involved in the development of allergic inflammation and airway hyperresponsiveness (AHR) in acute murine models. We hypothesized that functional inhibition of PAR2 prevents allergic inflammation, AHR and airway remodeling in chronic allergic airway inflammation models. Material and Methods: We developed and used a 12 week model of cockroach extract (CE)‐mediated AHR, airway inflammation and remodeling in BALB/c mice. Results: Mice sensitized and challenged with CE for 12 weeks exhibit AHR, increased numbers of eosinophils in bronchoalveolar lavage (BAL) and increased collagen content in the lung tissue compared to saline controls. Administration of an anti‐PAR2 antibody, SAM‐11, after the initial development of airway inflammation significantly inhibited all these parameters. Conclusions: Our data demonstrate that PAR2 signaling plays a key role in CE‐induced AHR and airway inflammation/remodeling in long term models of allergic airway inflammation. Targeting PAR2 activation may be a successful therapeutic strategy for allergic asthma.